EXPLORING POTENTIAL OF COASTAL RESERVOIRS FOR WATER RESOURCES DEVELOPMENT - MOHD TARMIZI, FARIDA HAMIMI (Universiti Teknologi PETRONAS, 2017)
Recently, water shortage in Malaysia is gradually becoming more severe and it is starting to cause problem in few areas. Few factors had contributed to the water shortage problem and it is identified that the most prominent cause is the increase of the water demand in an area. Therefore, alternative water supplies need to be explored in order to cater to the increasing water demand. In this study, coastal reservoir is suggested as one of the water alternative that should be explored in Malaysia. Coastal reservoir is a reservoir that is constructed at a river mouth where the river meets the ocean. Constructing the reservoir at the river mouth will have the advantage of the large catchment area where more than 90% of the runoff can be tapped as compared to the existing inland dams. The scope of this research is to analyse the water demand for the study area and to identify the current status of the water supply in the area.